From Lecture Theaters to Online Classrooms: Examining The Growth of the Flipped Classroom - Ouariach Soufiane; Ouariach Fatima Zahra; Khaldi Mohamed (COMPETITIVE: Journal of Education, 2024)
Traditional models of education involve teachers imparting knowledge to students in a classroom setting. However, new learning theories suggest that students do not all acquire information in the same way. Some learn better through independent exploration and discovery, while others thrive in social environments with hands-on instruction. This debate around student-centered versus teacher-centered pedagogy is far from resolved. One approach that is gaining attention is the "flipped classroom," which restructures learning activities so that domestic tasks typically done as homework are performed in class, with teacher guidance. Meanwhile, lectures previously given during class time are accessed autonomously by students at home, often via online video. This model arguably provides flexibility that better caters to varied student needs and learning styles. However, there are also challenges to consider when transitioning to a flipped model. This article explores the arguments on both sides, providing a balanced perspective on the benefits and limitations of traditional and flipped approaches based on current research in educational psychology. First, the article delves into the term "flipped classroom" and its relationship with the Bloom taxonomy. It then examines different flipped classroom models and finally the benefits and limitations of the flipped classroom application.